2019
DOI: 10.3389/fmicb.2019.02487
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella Phage KP34 RNA Polymerase and Its Use in RNA Synthesis

Abstract: We have characterized the single subunit RNA polymerase from Klebsiella phage KP34. The enzyme is unique among known bacteriophage RNA polymerases in that it recognizes two unrelated promoter sequences, which provided clues for the evolution of phage single-subunit RNA polymerases. As the first representative enzyme from the “phiKMV-like viruses” cluster, its use in run-off RNA synthesis was investigated. RNA-Seq analysis revealed that the KP34 RNA polymerase does not possess the undesired self-templated RNA t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…RNA polymerase and tail fiber genes were selected to investigate the genetic relationships between phages. RNA polymerase is a unique enzyme among phages 42 . The phylogenetic tree of RNA polymerase was constructed to confirm the relatedness of the phage.…”
Section: Discussionmentioning
confidence: 99%
“…RNA polymerase and tail fiber genes were selected to investigate the genetic relationships between phages. RNA polymerase is a unique enzyme among phages 42 . The phylogenetic tree of RNA polymerase was constructed to confirm the relatedness of the phage.…”
Section: Discussionmentioning
confidence: 99%
“…Beside the DNA-dependent RNA polymerase (DdRp) activity, T7 RNAP was found to retain the RNA-dependent RNA polymerase (RdRp) activity as well. T7 RNAP would catalyze RNA-primed RNA synthesis if the run-off RNA displays 3'-end complementarity to itself generating hairpin structure or to another RNA molecule forming intermolecular duplexes, yielding products longer than the run-off RNA (22,23,32,33). When we use WT T7 RNAP to synthesize the eGFP sgRNA (with terminal hairpin structure to mimic an RNA-primed RNA template structure), the 3' overextended transcripts from the RdRp activity shown as gel bands and smears moving slower than the run-off product bands in PAGE gel were clearly observed (32,33).…”
Section: S43y Mutation Attenuates the Rna-dependent Rna Polymerase Acmentioning
confidence: 99%
“…T7 RNAP would catalyze RNA-primed RNA synthesis if the run-off RNA displays 3'-end complementarity to itself generating hairpin structure or to another RNA molecule forming intermolecular duplexes, yielding products longer than the run-off RNA (22,23,32,33). When we use WT T7 RNAP to synthesize the eGFP sgRNA (with terminal hairpin structure to mimic an RNA-primed RNA template structure), the 3' overextended transcripts from the RdRp activity shown as gel bands and smears moving slower than the run-off product bands in PAGE gel were clearly observed (32,33). In this study when we investigate the termination efficiency of WT T7 RNAP and S43Y mutant on the class II terminator inserted in the eGFP sgRNA, we found that the S43Y mutation not only reduced the terminated products but also the overextended RNA products, resulting in significant increasing of run-off products ( Figure 4B).…”
Section: S43y Mutation Attenuates the Rna-dependent Rna Polymerase Acmentioning
confidence: 99%
“…Most mutants originate from T7 RNA polymerase, one of the most common single subunit RNA polymerases used, with a few reports describing the preparation of other RNA polymerase mutants. [16,17] T7 RNA polymerase mutants Results from mutagenesis experiments and structural analysis of the T7 RNA polymerase have revealed that amino acids R425, G542, Y639 and H784 are responsible for recognizing the 2'-OH of ribonucleotides (Figure 2). [15] Introducing amino acid substitutions for these residues have yielded T7 RNA polymerase mutants that are tolerant to ribose 2' modified ribonucleotide substrates.…”
Section: Rna Polymerases For the Synthesis Of 2' Modified Nucleic Acidsmentioning
confidence: 99%
“…Therefore, mutations to RNA polymerase have been introduced to change substrate specificity. Most mutants originate from T7 RNA polymerase, one of the most common single subunit RNA polymerases used, with a few reports describing the preparation of other RNA polymerase mutants [16,17] …”
Section: Enzymatic Synthesis Of Unnatural Nucleic Acidsmentioning
confidence: 99%